Average income, income inequality and export unit values - Hélène Latzer; Florian Mayneris (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
This paper analyses the relationship between a country's income distribution and its exports' unit values. Using bilateral export flows, we not only confirm the positive association between a country's average income and its export unit values, but further identify a heterogeneous relationship with income inequality: we find a greater income spread to be associated with higher exports unit values in the case of poor countries only. These results are robust to the inclusion of controls for other determinants of export unit values, as well as to the use of alternative measures of income inequality and of the quality index. We finally show that this heterogeneous relationship between income inequality and export unit values along the average income dimension is consistent with models emphasizing the role of the composition of local demand in determining the comparative advantage of countries in terms of quality.
Keywords: 330